2021
DOI: 10.3389/fimmu.2021.684823
|View full text |Cite
|
Sign up to set email alerts
|

Immunodominance of Epitopes and Protective Efficacy of HI Antigen Are Differentially Altered Using Different Adjuvants in a Mouse Model of Staphylococcus aureus Bacteremia

Abstract: HI, a fusion protein that consists of the alpha-toxin (Hla) and the N2 domain of iron surface determinant B (IsdB), is one of the antigens in the previously reported S. aureus vaccine rFSAV and has already entered phase II clinical trials. Previous studies revealed that HI is highly immunogenic in both mice and healthy volunteers, and the humoral immune response plays key roles in HI-mediated protection. In this study, we further investigated the protective efficacy of immunization with HI plus four different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Several studies have noted that some adjuvants are able to break immunodominance more effectively, driving epitope spreading, breadth, and durability 49,50 . In this context, several adjuvants have been shown to drive superior epitope targeting compared to alum [51][52][53] . Correlation analysis of IgG titers and Fc receptor binding for all four strains included in Gardasil® (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have noted that some adjuvants are able to break immunodominance more effectively, driving epitope spreading, breadth, and durability 49,50 . In this context, several adjuvants have been shown to drive superior epitope targeting compared to alum [51][52][53] . Correlation analysis of IgG titers and Fc receptor binding for all four strains included in Gardasil® (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The protective response induced by an antigen is largely mediated by its immunodominant epitopes [34], which has been proven in various viral infections, including in uenza virus [35], porcine epidemic diarrhea virus [36] and SARS-CoV-2 [37]. Immune responses induced by different immunodominant epitopes of the same antigen can result in different protective e cacies [11]. The results showed that RBD-mediated protection was altered in response to different adjuvants and immune routes.…”
Section: Discussionmentioning
confidence: 99%
“…The protective response induced by an antigen is largely mediated by its immunodominant epitopes [34], which has been proven in various viral infections, including in uenza virus [35], porcine epidemic diarrhea virus[36] and SARS-CoV-2 [37]. Immune responses induced by different immunodominant epitopes of the same antigen can result in different protective e cacies [11]. The results showed that RBD-mediated protection was altered in response to different adjuvants and immune routes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is pivotal to improve the immunogenicity of RBD for vaccine development. Previous studies have shown that both the vaccination strategy and adjuvants are crucial for enhancing the protective immune response [10], and adjuvants largely affect the immunodominance of epitopes and the protective e cacy of a given antigen [11]. In addition, SARS-CoV-2 infection is typically initiated from the mucosa of the respiratory tract.…”
Section: Introductionmentioning
confidence: 99%